Amandemen Konstitusi dalam Negara Demokratis : Studi Perbandingan Sistem Presidensial dan Parlementer - Siti Nuraidah; Floveina Azra; Azahra Vega; Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Constitutional amendments are crucial instruments in the dynamics of state governance, particularly in democratic countries that adopt either a presidential or parliamentary system. This study aims to analyze and compare the mechanisms, implications, and challenges of the constitutional amendment process in both systems. Using a descriptive-comparative approach, the research examines how each system designs and implements constitutional changes, including the role of the legislative and executive branches, as well as public participation. The findings indicate that the presidential system tends to have a more rigid amendment procedure compared to the parliamentary system, which is more flexible in enacting constitutional changes. These differences have implications for government stability, decision-making effectiveness, and the balance of power within each system. Therefore, a deep understanding of constitutional amendment mechanisms in different governmental systems is essential to ensure that constitutional changes remain aligned with democratic principles and national interests.